Baseline Thromboelastogram as a Predictor of Left Ventricular Assist Device Thrombosis. Issue 5 (July 2019) - Piche, Shannon L.; Nei, Scott D.; Frazee, Erin; Schettle, Sarah D.; Boilson, Barry A.; Plevak, Matthew F.; Dierkhising, Ross A.; Stulak, John M.
Abstract : Left ventricular assist device (LVAD) pump thrombosis occurs in up to 8.4% of patients within 3-months postimplantation. Thromboelastography (TEG) could be used to signal hypercoagulability at LVAD implantation to predict patients at high risk for thrombosis. We sought to evaluate whether TEG maximum amplitude (MA) hypercoagulability (MA ≥69 mm) at the time of LVAD implantation predicts pump thrombosis. A single center, retrospective, nested case–control study was conducted using patients from January 1, 2005, to March 31, 2015. Each pump thrombosis case was matched to two control subjects based on age ± 5 years, sex, and duration of follow-up. A multivariable logistic regression analysis was performed on the matched sets; the odds ratio with 95% confidence interval (CI) was calculated to estimate the relative risk. Thirty-seven age- and sex-matched case–control sets were included for a total of 111 study participants. TEG-MA hypercoagulability occurred in 10.8% of the case group versus 6.8% of controls. There was no association between TEG-MA hypercoagulability and device thrombosis (odds ratio 1.71, 95% confidence interval 0.42–7.05, p = 0.46). Utilization of baseline TEG-MA hypercoagulability to detect individuals at risk for LVAD thrombosis is a novel concept. This study found no significant association between TEG-MA and LVAD thrombosis.